2016
DOI: 10.1002/asia.201601614
|View full text |Cite
|
Sign up to set email alerts
|

An Obtuse‐angled Corner Unit for Fluctuating Carbon Nanohoops

Abstract: The invention of corner units was the key factor that allowed the synthesis of cyclo-para-phenylenes with strained curved π-systems. Despite only a few scarce instances of the development of corner units to date, a variety of structural congeners have been synthesized. These preceding corner units commonly possessed directing angles of ≤90°, which enabled the macrocyclization of multiple units, up to six. In this study, we introduce an obtuse-angled corner unit for the synthesis of cyclo-para-phenylene congene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 55 publications
0
32
1
2
Order By: Relevance
“…Ther ed shift of [3]CR was larger,s howing a + 140 nm shift for the onset absorption. [34] These cycloarylenes possess the same p-systems as the present [n]CR molecules but lack the pentagon bridges in the cyclic structures.T hus,b ased on this comparison, we can conclude that the p-conjugation is extended over the pentagon bridges as well as the biaryl linkages in the [n]CR molecules.A nother difference that resulted from the presence of the pentagons was noted in the fluorescence spectra. [32,33] This result shows that the p-conjugate system is extended in [n]CR from the monomeric rubicene.P reviously,w eh ave shown that relevant cycloarylenes with phenylene/anthracenylene panels commonly exhibit an onset absorption maximum at approximately 400 nm, independent of the number of panels.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Ther ed shift of [3]CR was larger,s howing a + 140 nm shift for the onset absorption. [34] These cycloarylenes possess the same p-systems as the present [n]CR molecules but lack the pentagon bridges in the cyclic structures.T hus,b ased on this comparison, we can conclude that the p-conjugation is extended over the pentagon bridges as well as the biaryl linkages in the [n]CR molecules.A nother difference that resulted from the presence of the pentagons was noted in the fluorescence spectra. [32,33] This result shows that the p-conjugate system is extended in [n]CR from the monomeric rubicene.P reviously,w eh ave shown that relevant cycloarylenes with phenylene/anthracenylene panels commonly exhibit an onset absorption maximum at approximately 400 nm, independent of the number of panels.…”
mentioning
confidence: 90%
“…TheA AA orientation of the rubicene panels that had been suggested by the solution-phase NMR analysis was thus confirmed. [34] Analyses of the bond lengths indicated that the quinoidal character was enhanced in the cylinder-shaped structure.F or instance,t he CÀCbond of [3]CR connecting C6 and C7 was shortened by 0.03 ,whereas the C4ÀC5 and C5ÀC6 bonds were extended by 0.04 (see Scheme 1f or the position numbers). [21] Ah armonic oscillator model of aromaticity (HOMA) was obtained from the crystal structures of [3]CR and rubicene.…”
mentioning
confidence: 99%
“…[32,33] This result shows that the p-conjugate system is extended in [n]CR from the monomeric rubicene.P reviously,w eh ave shown that relevant cycloarylenes with phenylene/anthracenylene panels commonly exhibit an onset absorption maximum at approximately 400 nm, independent of the number of panels. [34] These cycloarylenes possess the same p-systems as the present [n]CR molecules but lack the pentagon bridges in the cyclic structures.T hus,b ased on this comparison, we can conclude that the p-conjugation is extended over the pentagon bridges as well as the biaryl linkages in the [n]CR molecules.A nother difference that resulted from the presence of the pentagons was noted in the fluorescence spectra. The[ n]CR molecules were not fluorescent whereas the phenylene/anthracenylene cycloarylenes without pentagons do fluoresce.The effect of the pentagons on the excited states is of interest for further investigations in the future.…”
mentioning
confidence: 90%
“…[36] Another comparison of the HOMA values with relevant phenylene/anthracenylene cycloarylenes showed that the conjugation via pentagon bridges was also important for this reduced aromaticity ( Figure S3). [34] Analyses of the bond lengths indicated that the quinoidal character was enhanced in the cylinder-shaped structure.F or instance,t he CÀCbond of [3]CR connecting C6 and C7 was shortened by 0.03 ,whereas the C4ÀC5 and C5ÀC6 bonds were extended by 0.04 (see Scheme 1f or the position numbers).…”
mentioning
confidence: 99%
“…Arylene panel structures play key roles in deciding the numbers of panels participating in macrocyclization, and during our synthetic study of a sextuply helical molecule, we realized that a contorted aromatic panel of dibenzochrysene (denoted db C) could tune the panel numbers to form a narrow cylindrical macrocycle composed of chrysenylene units. Thus, in the db C panel, two boryl linkers were first installed at its 3,11‐positions via an 8‐step synthetic process starting from a commercially available compound (Figure ).…”
Section: Figurementioning
confidence: 99%